A Feasible Approach for Natural Products to Treatment of Diseases - Pak, Sok Cheon; Ooi, Soo Liang (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Introducing "A Feasible Approach for Natural Products to Treatment of Diseases"-an exploration of the therapeutic potential locked within nature's abundant offerings. This comprehensive reprint delves into the fascinating realm of natural products, uncovering their inherent properties, mechanisms of action, and potential roles in effective disease management. Through extensive scientific research and reviews, the authors shed light on the immense potential of natural products as a viable approach to enhancing health and combating diseases. This reprint presents a diverse and multidimensional exploration, bridging the gap between traditional wisdom and contemporary scientific understanding and offering new avenues for healthcare professionals, researchers, and enthusiasts to harness the power of nature's remarkable resources. As a catalyst for unlocking the healing potential of natural products, this reprint inspires further investigation and innovation, and drives us towards a future where their integration into mainstream healthcare becomes indispensable. Discover the possibilities and embark on a health and well-being journey with "A Feasible Approach for Natural Products to Treatment of Diseases".